Roles of intestinal Parabacteroides in human health and diseases. Issue 1 (9th August 2022) - Cui, Yanlong; Zhang, Leshan; Wang, Xin; Yi, Yanglei; Shan, Yuanyuan; Liu, Bianfang; Zhou, Yuan; Lü, Xin
Abstract: The stability of gut microbiota is essential for the host's health. Parabacteroides spp., core members of the human gut microbiota, have an average abundance of 1.27% in humans of 12 populations. Parabacteroides have recently been reported to have a close relationship with host health (e.g. metabolic syndrome, inflammatory bowel disease and obesity). Parabacteroides have the physiological characteristics of carbohydrate metabolism and secreting short chain fatty acids. However, antimicrobial resistance of Parabacteroides to antibiotics (such as clindamycin, moxifloxacin and cefoxitin) should not be ignored. In this review, we primarily focus on Parabacteroides distasonis, Parabacteroides goldsteinii, Parabacteroides johnsonii and Parabacteroides merdae and discuss their relationships with host disease, diet and the prevention or induction of diseases. Pa. distasonis and Pa. goldsteinii may be viewed as potential next generation probiotic candidates due to their protective effects on inflammation and obesity in mice. We also discuss the potential therapeutic application of Parabacteroides spp. in maintaining host–intestine homeostasis. Abstract : Parabacteroides spp. are closely associated with human health and diseases. Parabacteroides distasonis and Parabacteroides goldsteinii are potential next-generation probiotics.